Sociopreneurship sebagai Alternatif Pemberdayaan Masyarakat dan Pengentasan Kemiskinan - Dian Arlupi Utami; Noviyanti Noviyanti; Gading Gama Putra; Agus Prasetyawan (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2017)
Not the secret of Indonesia's social and economic problems are poverty and unemployment. Sociopreneuship as an economic driver, provides business opportunities, business views and practical aspects in solving social and economic problems. In addition to macroeconomic improvements, sociopreneurship is a solution to improve the national economy. This paper describes sociopreneurship, poverty, theoretical community empowerment and best practice sociopreneurship in Indonesia